Muscone Reduces OGD/R-Induced Hyperpermeability of the Brain Endothelial Barrier by Activating the PKA/RHOA/MLC Pathway - Yang, Ziteng; Zuo, Yuanqi; Wang, Guangyun; Wang, Ning (Current neurovascular research, 2025)
The endothelial barrier is composed of brain microvascular endothelial cells (BMECs) and tight junction (TJ) proteins. Musk is a valuable ingredient in Traditional Chinese Medicine (TCM). It is used in the treatment of stroke because of its ability to induce resuscitation. The core component of musk is muscone. Previous studies have evidenced that muscone may be involved in the treatment of ischemic stroke (IS), but the underlying mechanism is still unclear. The main objective of this study was to explore the protective effect of muscone on OGD/R-induced endothelial barrier disruption and determine its underlying mechanism. OGD/R-induced damage to BMECs was assessed using the MTT and LDH assays. The apoptosis level in BMECs was determined using western blot and Hoechst staining. Western blot, immunofluorescence, and phalloidin staining were used to assess the expressions of TJ proteins and pathway proteins expression. A monolayer cell barrier was constructed using BMECs in vitro, and the permeability of the barrier was assessed by TEER as well as the transmissivity of sodium fluorescein. Molecular docking, DARTS, and CETSA were used to verify the regulatory effect of muscone on the pathway. Muscone reduced OGD/R-induced apoptosis of BMEC cells, inhibited the degradation of TJ proteins, promoted the coherent expression of ZO-1 on the membrane, and restored TEER. Mechanistic studies showed that H-89 reversed the promoting effects of muscone on pathway proteins and promoted the disassembly of the actin cytoskeleton, which, in turn, promotes BMEC apoptosis and TJ protein degradation, ultimately disrupting the endothelial barrier. We demonstrated that muscone could reduce OGD/R-induced hyperpermeability of the brain endothelial barrier by activating the PKA/RHOA/MLC pathway.